UPAYA INDONESIA BEKERJASAMA DENGAN ASEAN COMMISSION ON THE PROMOTION AND PROTECTION OF THE RIGHTS OF WOMEN AND CHILDREN (ACWC) DALAM MENANGGULANGI PERDAGANGAN PEREMPUAN DAN ANAK DI INDONESIA - Ayu Oktaviana Kurniadewi; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research discusses Indonesia's efforts with ASEAN to tackle the trafficking of women and children within the framework of the ASEAN Commission on the Promotion and Protection of the Rights of Women and Children. Indonesia has become a place of delivery, transit, and trafficking destinations for women and children. To tackle the trafficking of such people, Indonesia cooperates with acwc. What are the efforts made by Indonesia? And what is the result of cooperation between Indonesia and ACWC?This research uses qualitative research methods using the perspective of constitutional Neoliberalism with the analysis of international Organizational Theory to analyze cases. The findings of the study from indonesia and ACWC cooperation resulted in guidelines in the form of Regional Action Plan on the Elimination of Violence against women and Action Plan on The Elimination of Violence Against Children.Keyword: Trafficking, People, ACWC, Elimination of Violence, Gender sensitivity